1986
DOI: 10.1159/000184217
|View full text |Cite
|
Sign up to set email alerts
|

Intraabdominal Pressures during Natural Activities in Patients Treated with Continuous Ambulatory Peritoneal Dialysis

Abstract: Intraabdominal pressures were measured during natural activities in 6 men, age 24–62 years, treated with continuous ambulatory peritoneal dialysis. The pressures were measured with a pressure transducer secured at the level of the umbilicus in the supine, sitting, and upright positions with 0–3 liters intraperitoneal fluid during talking, coughing, straining, changing position, walking, jogging, exercycling, jumping and weight lifting. Coughing and straining generated the highest intraabdominal pressures in ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(85 citation statements)
references
References 11 publications
(18 reference statements)
3
79
0
3
Order By: Relevance
“…In a previous report, low body weight was associated with abdominal hernia formation in PD patients [18]. In another report, BMI was not a risk factor for hernia development in PD patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, low body weight was associated with abdominal hernia formation in PD patients [18]. In another report, BMI was not a risk factor for hernia development in PD patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…22 Changes in posture, coughing and straining in the sitting and upright positions generate higher intraperitoneal pressure for a given activity. 23,24 All types of hernias are described. Six (10%) of our patients developed hernias, which is comparable to 11.5% reported in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…11 The effect of intraperitoneal pressure (IPP) on GERD in per- itoneal dialysis, which can be explained by decreased basal tone of the lower esophageal sphincter. 11,12 In contrast, a manometric study showed no effect of dialysate infusion on lower esophageal sphincter pressures due to transient relaxation of lower esophageal sphincter function. 13 The aim of this study was to determine the differences in the prevalence of erosive reflux esophagitis (ERD) and nonerosive reflux esophagitis (NERD) between CKD patients undergoing peritoneal dialysis and those undergoing hemodialysis.…”
Section: Introductionmentioning
confidence: 99%